Achieving dynamic stability and electromechanical resilience for ultra-flexible battery technology - Sam Riley; Andrew Shevchuk; Chandramohan George (Communications Materials)
Abstract Despite the huge potential of mechanically flexible batteries in healthcare, robotics, transportation and sensing, their development towards real-world applications is stalled due to issues such as capacity decay, limited energy/power density at any given pliability, compromised safety and poor packaging. These issues originate from design flaws, electromechanical degradation and underdeveloped characterisation of composite electrodes, lacking direct correlations between mechanical flexibility and electrochemical performance. Here, we review the state-of-the-art advances in Li-based flexible electrodes, cell architectures and materials and discuss the correlations between electrode microstructure, electrochemical trends, mechanical pliability and safety, emphasising the need for improved metrology and standardisation quantifying electromechanical resiliency.